Analysis of the Role of Housewives and the Contribution of Culinary Businesses in Increasing Household Income - Mispandi, Mispandi; Fahrurrozi, Muh.; Andani , Ulia Rizki (Economic Education Analysis Journal, 2024)
This study aims to analyze the role of housewives and the culinary contribution of cakes to household income in Kelayu Village. This type of research is descriptive qualitative research and the data sources in this research are primary data and secondary data. Data collection was obtained by means of interviews and observations as well as questionnaires. Sampling using the Simple Random Sampling method with random sampling technique. Data collection was obtained by conducting research in the form of in-depth interviews with information on the husband and wife of cake culinary business actors, both individually and together using a prepared questionnaire. Analysis of the data used in this study using descriptive analysis and will be presented in the report. Based on the research results, the role of a housewife is to cook, clean, wash and meet the needs of her husband and children and sell or open a business. However, with the work done by housewives, they do not forget their obligations and duties as a housewife. Housewives help their husbands to increase family income, husbands don't mind even supporting their wives in participating in meeting family needs. With the business of selling traditional cakes, it even has a positive impact on families and contributes to the income of housewives through culinary cakes to family income, namely 54.55% and it can be concluded that the income contribution of housewives to large family income is > 50%. The existence of this cake selling business is very helpful for housewives in increasing family income and helping reduce the burden on husbands in supporting their family.